Dal «Comentum» al «Commento». Il volgarizzamento delle chiose petrine all’«Inferno» tràdito dal ms. Ashburnham App. Dantesca 2 (Carte Romanze, 2024)
The essay is based on the study of the only integral vulgarization known today of the first draft of Pietro Alighieri’s Comentum, conveyed by the ms. Ashburnham Appendice Dantesca 2 of the Biblioteca Medicea Laurenziana of Florence. In particular, the analysis focuses on the commentary of the Inferno, whose relationship with the Latin source is investigated for the first time. Starting from a selection of glosses considered exemplary, an attempt is made to identify in which branch of the Latin tradition the source of the codex lies. Then, the main types of changes made on the text and perhaps mediated by the model are presented. In conclusion, a possible contamination of the vulgarization through the use of the two later drafts is evaluated.
Keywords: Dante; Pietro Alighieri; Comentum; translation into vernacular